Construction of a chamber for in situ monitoring of the drying process of gels and porous solids - Passos, Aline Ribeiro [UNESP]; Martins, Leandro [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP] (My University, 2011)
The present work deals with the design and construction of an equipment for studying the drying process of gels and solids. The equipment was built using mainly a commercial oven and others peripherals for programmed control of temperature, humidity and data acquisition. The system allows the in situ monitoring of the gel drying, registering the weight loss, and the shrinkage of sample and the oven temperatures. This set of allowed parameters makes possible to establish the main steps involved in the drying of meso and nanostructured porous materials.
Construção de uma câmara para monitoramento in situ do processo de secagem de geis e sólidos porosos
Keywords: Gels drying; Shrinkage; Equipment design